Disorders of nutritional status in sepsis – facts and myths - Katarzyna Kosałka; Ewelina Wachowska; Robert Słotwiński (Gastroenterology Review)
The problem of diagnosing nutritional status disorders in septic patients remains unresolved. This is associated with the necessity of the introduction of newer and newer methods of assessing nutritional status, often requiring precise and expensive equipment as well as employment of professionals in this field in hospital wards, primarily including intensive care units (ICU). Methods that have been applied thus far for assessing nutritional status, also used in severely ill septic patients, have little impact on improving treatment results. This is due to the high dynamics of changes in nutritional status in these patients, healing process variability in individual patients, and the “mismatch” of methods for assessing nutritional status in relation to the patient’s clinical status. The diagnostic value of the traditional methods of assessing nutritional status, i.e. anthropometric analysis and selected laboratory tests, as markers of nutritional status disorders in septic patients, is still debatable. There is still no precise method that could become the “gold standard” allowing for early identification of malnutrition in these group of patients. Phase angle, bioelectrical impedance vector analysis (BIVA), and the “illness marker”, obtained directly from the resistance, reactance, and impedance, can be used as prognostic or nutritional indices in severely ill septic patients, but the intensity of research on this subject needs to be increased. Detailed assessment of nutritional status should include tests of selected inflammation markers (including TLC, HMGB1, IL-6, IL-10, IL-1ra, sTNFRI).